Construction and application of the Shenzhen Intelligent Campus Health Management System - Yu WU; Qian WANG; Haiyuan DING; Xiaoheng LI; Changyong LI; Kefan CHEN; Jinquan CHENG (Editorial Office of Chinese Journal of Public Health, 2023)
Information technology is one of effective means to promote school health implementation. However, the existing school health information systems are fragmented, isolated, and lack of integration and suffer from serious information barrier. Additionally, some of the existing systems have incomplete functions, low level of intelligence, and slow update and iteration, witch seriously restricting the development of school health informatization. To break through the information barrier and promote the development of school health informationization, as well as to provide scientific means to improve the level of school health management and student health, it is imperative to build a smart and integrated school health management system platform. In this article, we briefly presented construction goal, technical framework, application, and utilization effects of the Shenzhen Intelligent Campus School Health Management System.